Donor-Site Morbidity of Free Muscle and Perforator Flaps: Comparison of the Gracilis Muscle Flap and the Anterolateral Thigh Flap - Fricke, Alba; Rassner, M.; Kiefer, J.; Bannasch, H.; Stark, G. B.; Eisenhardt, S. U. (Journal of Reconstructive Microsurgery, 2017)
Background Both the gracilis muscle flap and the anterolateral thigh (ALT) flap have been described as successful reconstructive options for defect coverage after trauma or tumor resection. In general, free perforator flaps are considered to generate less donor-site morbidity than muscle flaps. Here, we put this hypothesis to the test.Methods In this study, 193 patients who had undergone free flap reconstruction with either free gracilis muscle flaps (n = 131) or ALT flaps (n = 62) were included. Subjective patient satisfaction with the aesthetic and functional outcome of the donor sites was assessed using a self-report questionnaire as well as the Lower Extremity Functional Scale (LEFS).Results Comparing the donor-site morbidity of free ALT and gracilis flaps, the LEFS revealed no significant differences in functional impairment (p = 0.6447) of the lower extremity. The donor-site scar was significantly longer after ALT flap harvest (mean: 21.16 cm) than after gracilis muscle flap harvest (mean: 14.17 cm; p < 0.0001). Furthermore, donor-site numbness was significantly greater in the ALT group than in the gracilis group (p = 0.0068).Conclusion No significant differences in functional impairment of the lower extremity were reported after gracilis muscle and ALT flap harvest. Regarding scar length and level of numbness of the donor site, the gracilis muscle flap was shown to be superior to the ALT flap.
Keywords: anterolateral thigh flap; gracilis flap; donor-site morbidity